Precalculus: Concepts Through Functions, A Unit Circle Approach to Trigonometry (3rd Edition)

Published by Pearson
ISBN 10: 0-32193-104-1
ISBN 13: 978-0-32193-104-7

Chapter 11 - Sequences; Induction; the Binomial Theorem - Section 11.3 Geometric Sequences; Geometric Series - 11.3 Assess Your Understanding - Page 844: 27


The $n^{th}$ term of the geometric sequence is: $a_n=1 (\dfrac{1}{2})^{n-1}$ and $a_7=\dfrac{1}{64}$

Work Step by Step

The $n^{th}$ term of the sequence is given by the formula: $ a_n=a_1r^{n-1}$ where $r$=common ratio and $a_1$= the first term The common ratio of a geometric sequence is equal to the quotient of any term and the term before it: $ \ r = \dfrac{a_n}{a_{n-1}}$ or, $r=\dfrac{a_2}{a_1}=\dfrac{1/2}{1}=\dfrac{1}{2}$ Therefore, the $n^{th}$ term of the geometric sequence is: $a_n=1 (\dfrac{1}{2})^{n-1}$ Now, the 7th term can be computed by substituting $7$ for $n$: $a_7=1 (\dfrac{1}{2})^{7-1}=(\dfrac{1}{2})^{6}=\dfrac{1}{64}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.